Numerical simulation of the vertical migration of Microcystis (cyanobacteria) colonies based on turbulence drag - Hongru Zhao; Wei Zhu; Huaimin Chen; Xiaohua Zhou; Ruochen Wang; Ming Li (Journal of Limnology, 2016)
The vertical migration and accumulation of Microcystis is an important process in water blooms, and colony migration is influenced by colony size and wind-wave disturbance. The vertical migration of Microcystis colonies in turbulence can be simulated in a numerical model. In this study, we model such migration by coupling the colony size and hydrodynamics, including the gravity, colony buoyancy, and the viscous drag force of turbulence. The turbulence intensity was represented by the turbulent kinetic energy (KZ); the larger the KZ, the stronger the wind-wave disturbance. The simulated vertical distribution of Microcystis well agreed with the measured values in a laboratory experiment indicating that our model can simulate the vertical distribution of Microcystis under different hydrodynamic conditions. We also found a size-dependent critical turbulent kinetic energy (TKZ), such that if the turbulent kinetic energy of water exceeds the critical value (i.e., KZ > TKZ), the colonies sink under the drag forces of turbulence; conversely, if KZ < TKZ, the colonies can overcome the turbulent mixing and float. The TKZ of each colony was linearly related to colony diameter. The model is crucial for prediction and prevention of water blooms. The simulated threshold turbulent kinetic energy, at which water blooms disappear in Lake Taihu (a large freshwater lake in the Yangtze Delta, Jiangsu Province, China), was 55.5 cm2 s−2.